STUDI KETERAMPILAN PROSES SAINS SISWA KELAS VI DI SD N MANDUANG - Prianja Resti, Ni Komang Ria; Ni Wayan Sri Darmayanti (ITP Markandeya Bali, 2025)
This research aims to describe the level of science process skills of class VI students at SDN Manduang. The research subjects consisted of 17 students and one teacher. The instruments used include questionnaires, interview guides, and documentation. Data analysis was carried out descriptively quantitatively using a Likert scale. As a result, in general students are quite good at carrying out scientific activities. As many as 45% of students were rated very good, 35% good, and the rest quite good. The findings from this research can be important input for developing better ways of teaching science in elementary schools. This research wants to see how well grade 6 students at Manduang Elementary School use scientific thinking skills in science learning.